Revolutionizing Early Education through Advanced Speaking Skills Approach: Merevolusi Pendidikan Anak Usia Dini melalui Pendekatan Keterampilan Berbicara Tingkat Lanjut - Ni’mah, Alfa; Destiana, Evie (Indonesian Journal of Education Methods Development, 2024)
This study implemented the show and tell method to enhance the speaking skills of 5-6-year-old children at Wonosari Muslimat Kindergarten. Using the Classroom Action Research (PTK) approach with collaborative planning, implementation, and reflection, data were collected through observation, interviews, and documentation. Results showed significant improvement, reaching 77.47% proficiency in the second cycle, meeting the 75% target. This research highlights the effectiveness of the show and tell method in improving early childhood speaking skills. Highlight: Show and Tell: Boosting Speaking Skills Early Childhood Education: Language Development Focus Action Research: Collaborative Improvement Approach Keyword: Show and Tell Method, Speaking Skills, Early Childhood Education, Classroom Action Research, Improvement.